PREPARING FUTURE TEACHERS FOR INNOVATIVE PEDAGOGICAL ACTIVITIES - A. R. Khasanov; F. H. Saliyeva (Galaxy International Interdisciplinary Research Journal, 2023)
The demand and needs for highly qualified pedagogues in the development and progress of new Uzbekistan are increasing day by day. In particular, it is necessary to train creative pedagogues who have the ability to educate the mature generation in the spirit of universal and national values that have been formed for centuries, who have mastered the fundamentals of science, pedagogy and psychology methods, who have a high level of professional training and who have the skills and qualifications to apply modern pedagogical and information technologies in practice. In the process of higher pedagogical education, there is an opportunity to form a student personality who can meet these requirements and has quality knowledge, skills and qualifications. For this, there is a growing demand for the wide application of modern approaches and innovations in the process of higher pedagogical education aimed at preparing future teachers for professional and pedagogical activities.